Central Giant Cell Granuloma of Posterior Maxilla: First Expression of Primary Hyperparathyroidism - Deepanshu Gulati; Vishal Bansal; Prajesh Dubey; Sanjay Pandey; Abhinav Agrawal (Case Reports in Endocrinology)
A case of 19-year-old male patient reported with the chief complaint of slowly growing diffuse painless swelling over the right part of the face from last 6 months. Intraoral examination revealed a swelling on right side of palate in relation to molar region with buccal cortical plate expansion. Radiographic examination (orthopantograph and 3DCT) showed large multilocular radiolucency in right maxilla with generalized loss of lamina dura. Incisional biopsy was done and specimen was sent for histopathological examination which showed multinucleated giant cells containing 15–30 nuclei. Based on clinical, radiological, and histopathological findings provisional diagnosis of central giant cell granuloma was made. Blood tests after histopathology demonstrated elevated serum calcium level and alkaline phosphatase level. Immunoassay of parathyroid hormone (PTH) level was found to be highly elevated. Radiographic examination of long bones like humerus and femur, mandible, and skull was also done which showed osteoclastic lesions. Considering the clinical, radiographic, histopathological, and blood investigation findings, final diagnosis of brown tumour of maxilla was made. The patient underwent partial parathyroidectomy under general anaesthesia to control primary hyperparathyroidism. Surgical removal of the bony lesion was done by curettage. The patient has been followed up for 1 year with no postoperative complications and the lesion healed uneventfully.